Analysis of the results of Wayground-Based formative assessments on the learning outcomes of High School Students' biographical texts - Galih Ramadhan; Dede Endang Mascita; Jimat Susilo (Jurnal Bebasan, 2025)
Formative assessments have a strategic role in providing feedback that helps improve student learning outcomes. This study aims to analyze the effectiveness of the Wayground digital platform as a formative assessment medium in learning biographical texts in class X of SMA Negeri 1 Kawali. The method used is quantitative descriptive by involving students as research subjects through the presentation of multiple-choice tests on conventional media and the Wayground platform. The results of the study show that the use of Wayground can increase student engagement and strengthen the quality of feedback during the learning process. These findings affirm Wayground's pedagogical contribution as an alternative to digital assessment that supports monitoring learning outcomes more effectively and relevant to the demands of 21st-century learning.